(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the intraoperative, early postoperative, and short-term follow-up outcomes of nephrectomy for benign non-functioning kidneys performed with Artisential-assisted retroperitoneoscopic surgery. Subjects and methods: This was a descriptive study combining retrospective and prospective data on 73 patients diagnosed with non-functioning kidneys secondary to benign obstructive uropathy who underwent Artisential-assisted retroperitoneoscopic nephrectomy at Thanh Hoa provincial General Hospital from January 2022 to June 2025. Outcome measures included operative time, Artisential use time, blood loss, transfusion, intraoperative adverse events, and conversion to open surgery; postoperative recovery parameters (VAS pain score, time to first flatus, drain removal, and postoperative hospital stay); postoperative complications classified by Clavien-Dindo; and 1 to 3 months follow-up findings including laboratory tests and renal fossa fluid collection on ultrasonography. Results: The mean age was 61.1 ± 13.9 years, and females predominated (74%). Intraoperatively, grade 3-4 adhesions were found in 32.9% of cases, and pyonephrosis was present in 22.7%. Median blood loss was 60 mL (range, 12-500 mL); the transfusion rate was 6.8%; intraoperative adverse events occurred in 1.4%; and no case required conversion to open surgery. Mean ArtiSential use time was 28.3 ± 11.6 minutes, and mean total operative time was 71.6 ± 24.5 minutes. Postoperatively, the mean VAS score was 3.3; the mean times to first flatus, drain removal, and postoperative hospital stay were 1.3; 7.1, and 8.2 days, respectively. The postoperative complication rate was 15.1%, mostly Clavien-Dindo grade 1-2, with one grade 3b case requiring re-laparoscopy. During follow-up to 3 months, serum creatinine increased and eGFR decreased significantly over time, while renal fossa fluid collection declined from 18.8% at discharge to 0% at 3 months. Conclusions: Retroperitoneoscopic nephrectomy for benign non-functioning kidneys with Artisential instrument assistance at Thanh Hoa provincial General Hospital was shown to be feasible and safe. The mean operative time was 71.6 minutes, the intraoperative complication rate was low (1.4%), and postoperative complications occurred in 15.1% of cases, predominantly Clavien-Dindo grade 1-2.